INNOVATIVE APPROACHES TO SEWING DESIGN: A FUSION OF TRADITION AND TECHNOLOGY - Ortikova Ozoda Sharofovna (American Journals Publishing, 2025)
Sewing design, a traditional craft that has evolved over centuries, is experiencing a renaissance through innovative approaches that combine traditional techniques with modern technology. This article explores the intersection of tradition and innovation in sewing design, highlighting how advancements in materials, tools, and techniques are revolutionizing the way garments are conceptualized and created. From 3D printing to smart textiles, the possibilities for creativity in sewing design are endless. By embracing these innovative approaches, designers can push the boundaries of traditional garment construction and create truly unique and cutting-edge pieces.
Keywords: Centuries, Sewing design, Technology, innovative approaches, smart textiles, the border between fashion and technology.